2019
DOI: 10.1177/1473225419872406
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Rural Youth and Role Tension of the Police: ‘It’s Hard in a Small Town’

Abstract: This article presents findings from a case study examining youth perceptions of the police in rural areas of Eastern Canada. A total of 20 semistructured focus group discussions were conducted with 60 youth from Canadian rural Atlantic areas, who were purposively recruited, with groups stratified by age and gender. Discussions centered on role tension regarding the police’s role, that is, along a continuum between law enforcement and public protection versus community policing and crime prevention. Our discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…For example, research has shown that policing practices affecting young people, such as stop-and-search, constitute barriers to their social participation (D. M. Brown, 2013; Brunson & Miller, 2006; Francis, 2021; Kennelly, 2011; Murray et al, 2021; Ricciardelli et al, 2020; Sharp & Atherton, 2007). However, participants of this study did not mention any encounters with law enforcers, such as the police, in describing barriers to inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, research has shown that policing practices affecting young people, such as stop-and-search, constitute barriers to their social participation (D. M. Brown, 2013; Brunson & Miller, 2006; Francis, 2021; Kennelly, 2011; Murray et al, 2021; Ricciardelli et al, 2020; Sharp & Atherton, 2007). However, participants of this study did not mention any encounters with law enforcers, such as the police, in describing barriers to inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…According to P. Kelly (2003), increasingly, there is a "generalized and institutionalized anxiety and mistrust in relation to the capacities of today's young people to make the transition to adulthood" (p. 166). The consequence is to criminalize young people for policing in order to keep public spaces sanitized (D. M. Brown, 2013;Brunson & Miller, 2006;Francis, 2021;Kennelly, 2011;Murray et al, 2021;Ricciardelli et al, 2020;Sharp & Atherton, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Z zadovoljstvom s policijo je povezana starost prebivalcev in njihove predhodne izkušnje s policijo (Hwang et al, 2005;Lytle in Bolger, 2017). Raziskava v Kanadi je pokazala, da mladi v manjši meri zaupajo policistom, ki so bolj vpeti v skupnost, saj menijo, da so lahko bolj pristranski (Ricciardelli, Adorjan in Spencer, 2020). Mlade prestopnike policisti različno obravnavajo, glede na vrsto kaznivega dejanja in nespoštljivo vedenje mladostnikov.…”
Section: Rezultatiunclassified
“…Alternatively, the program is offered in a location (often rural or remote) where the program has broad service offerings, occasionally with the opportunities to offer personalized support to individual clients based on their needs. Generally, these services do their best with the resources available to them but lack the resources to provide targeted or specialized programming (Higginbottom et al, 2016;Levasseur et al, 2015;Ricciardelli, Adorjan, & Spencer, 2020). For example, a more remote community might have the resources to support a client through detox but is unable to offer long-term programming in addictions support or sobriety maintenance.…”
Section: Organization-specific Specialized Programsmentioning
confidence: 99%